Internet Memes, Media Frames, and the Conflicting Logics of Climate Change Discourse. Issue 7 (3rd October 2019) - Ross, Andrew S.; Rivers, Damian J.
ABSTRACT: Media frames have been applied to news information for decades to influence the manner in which news is both delivered and interpreted. However, media frames have tended to focus on traditional news media channels, but the emergence of new media platforms now necessitates a recalibration of how media framing is understood in relation to media and communication studies. With a focus on the issue of climate change, this study explores how framing is employed by the phenomenon of Internet memes in the new media landscape. Specifically, memes presented demonstrate the representation of five common media frames from the perspectives of both the "convinced" and "skeptical" logics. It is argued that through the use of common meme templates combined with the typical humorous or ironic message they convey, Internet memes represent a potentially powerful form of socio-political participation in the online community.